Where do children's rights come in?. (2nd May 2022) - Meechan, David
Abstract : This is the third article in the series 'We need to talk about tracking' . The previous two have looked at practitioner perspectives (Sept 2021) and parent perspectives (Feb 2022) of assessment. This article will introduce the idea of a rights based approach and consider key people involved in assessment processes in the early years.